Audience participation in Xu Bing’s works: transcultural issues in global contemporary Art - Xu, Bing; Fraser, Sarah E.; Juneja, Monica; Mittler, Barbara; Hopfener, Birgit; Trede, Melanie (Xu Bing, 2020)
This is an edited transcription of the third Xu Bing event—a roundtable discussion on July 16, 2015, moderated by Professor Dr. Sarah E. Fraser. Xu’s address was delivered as Distinguished Visiting Professor supported by the Heinz Götze Foundation. He provides a brief overview of his recent works post-2000s that engage the audience with different mediums, including projects that involve the aesthetics of the working class, archival material, and computer programming. The panelists offer remarks on issues associated with audience participation and transculturality. Professor Dr. Monica Juneja raises questions about authorship and transculturality in participatory projects. Professor Dr. Barbara Mittler analyzes three contradictions in participatory art, including traditional and socialist aspects of art in the Chinese context, beauty in social art projects, and Zen and meaningless meaning. Dr. Birgit Hopfener argues that Background Story transforms the viewers’ awareness of their positions in relation to historiography; she asks whether the act of the audience generating meaning can be interpreted as a contemporary form of cultivation and if it is possible to build transcultural communities through art. Professor Dr. Melanie Trede’s presentation includes an analysis of how Xu uses specific strategies that demand careful readings of the works from the audience. She also draws connections between Background Story and painting techniques in eighteenth-century Japan.
Gesehen am 02.11.2023